Perceptions of anti-racism efforts and mental health among students in higher education in the United States - Oh, Hans; Karcher, Nicole R.; Besecker, Megan; DeVylder, Jordan E.; Lincoln, Karen D. (Frontiers in Public Health, 2025)
BackgroundAnti-racism efforts are imperative for campus communities, yet little is known about whether perceiving their presence on campuses relates to a range of mental health outcomes among students.MethodsWe analyzed data from the Healthy Minds Study 2020–2021 (N = 110,203). Using multivariable logistic regression, we examined the associations between perceptions of anti-racism efforts and several mental health outcomes.ResultsIndividuals who disagreed that their schools combatted racism in their campus communities had significantly greater odds of mental health problems (depression, anxiety, psychotic experiences, suicidal ideation, suicide plan, suicide attempt, perceived need for help, and loneliness), and lower odds of flourishing when compared with those who strongly agreed with the statement. For most outcomes, we observed an apparent dose–response association.ConclusionPerceiving the presence of anti-racism efforts on campuses was inversely associated with mental health problems, calling for more research to test the effects of anti-racism efforts on mental health.